How smallholder farmers adapt to climate change: Stories from India—Dr. R.P. Singh - Singh, R.P. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Dr. R.P. Singh, Deputy Faculty, Dept of Plant breeding and Genetics at the Punjab Agricultural University describes the decreased water availability due to climate change and how they are working to select crop varieties that need less water and to help farmer to make better use of irrigation.